Respuesta :

2y = -4
Y= -2

X= -4

Don’t even thank :))
x + 2y = -4
 For this case what you should do is see the intersections with each of the axes and then join the ordered pairs.
 We have then:
 For the x axis:
 y = 0
 Substituting in the equation:
 x + 2 (0) = - 4
 x + 0 = -4
 x = -4
 For the y axis:
 x = 0
 Substituting in the equation:
 x + 2y = -4
 0 + 2y = -4
 y = -4 / 2
 y = -2
 We graph the ordered pairs:
 (x1, y1) = (- 4, 0)
 (x2, y2) = (0, -2)
 Answer: 
 See attached graph.
Ver imagen carlosego